Optimasi Kombinasi Bahan Makanan untuk Meningkatkan Imunitas dan Pencegahan Dini Tertular Covid-19 pada Usia Dewasa Muda menggunakan Algoritma Genetika - Anggi Novita Sari; Imam Cholissodin; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The Covid-19 pandemic is a new virus that attacks the body's immunity, various steps and efforts have been made to prevent transmission of the virus. The problems experienced are that the spread of Covid-19 is very fast, lack of exercise and high stress levels can weaken the body's immunity, and a poor diet can worsen the body's immunity. And there is no computer-based system to determine the combination of food ingredients as a form of early prevention of contracting Covid-19. The Ministry of Health provides an appeal for the fulfillment of balanced nutrition to increase body immunity so that it can reduce the risk of chronic diseases and infections with optimal nutrition to build or improve the body's immunity to work properly. In solving optimization problems, genetic algorithms can be used, which are effective in solving optimization problems with chromosomal variations obtained through the basis of biological evolution with a wide search space, so that they are not trapped in the local optimum. This study provides recommendations for food ingredients that can be consumed for 2 days and in consultation with nutritionists. Based on the test, the most optimal results are obtained with a combination of the values ​​of cr 0,3 and mr 0,7 with an average fitness value of 0,848, a population size of 160 with an average fitness value of 0,917, and the number of generations 241 with an average fitness value of 1,076. And can save expenses by 33% in a day with an average cost of Rp26.800 for men and 42% for women with an average cost of Rp23.350.